The Horizon effect: A counterfactual analysis of EU research & innovation grants - Alessio Mitra; Konstantinos Niakaros (Publications Office of the European Union, 2023)
This paper evaluates the causal impact of the Horizon 2020 Framework Programme for Research and Innovation on financial firm-level outcomes using a Difference-in-Differences (DiD) approach. We use administrative data from CORDA and financial data from ORBIS spanning from 2010 to 2022, for a sample of approximately 40 thousand unique private companies that applied for Horizon 2020 funding. The findings suggest that firms receiving Horizon 2020 grants exhibit an average increase of 20% in employment and about 30% in total assets and revenues, compared to comparable companies in the control group, in the years after receiving their first grant. Positive effects persist even after 2.5 years, which is the average duration of a project in our sample. Companies in the “Information and communication” and “Professional, scientific and technical activities” NACE sectors are driving the results, while other sectors show insignificant effects.
Keywords: G38; L52; O38; D22; 330; Horizon 2020; Difference-in-Differences; European Union; Innovation policy